Problem Analysis and Development Strategy for Ikat Weaving Bandar Kidul Kediri, East Java - Bella Para Dita; Bella Arum Kristanti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Weave Bandar Kidul is a craft of the Kediri which has become an icon of Kediri. Weaving Bandar Kidul Kediri weaving center is the economic supportfor the people of Kediri. Weaving Bandar Kidul Kediri must be improved its existence and development. This research aims to increase the income of the people of Kediri and seek to introduce the Bandar Kidul Kediri weaving to the community. The researcher used a quantitative approach by taking random purposive sampling of weaving craftsmen in Bandar Kidul Kediri. This study examines the effect of length of business, labor, total cost and capital on the total income level of bandar Kidul Kediri ikat weaving. The data used in the form of primary data and secondary data in the form of questionnaires and interviews.